Review of Community Service Activities in the Field of History Education: Ulasan Kegiatan Pengabdian Masyarakat di Bidang Pendidikan Sejarah - Miskawi; Maulana Yusuf Arrasuly (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Many community service activities have been carried out and published. The aim of writing this article is to review community service activities in the field of history education. The review was carried out by searching online-based activity publications. The search results are summarized and grouped according to year, partner or target group, activity theme and activity method. Analysis was carried out for the number of publications according to grouping categories. The results of the review show a trend towards an increase in the number of publications. Many history teachers become partners in activities with learning themes and carried out using socialization methods.